Acupuncture for tumor-related depression: a systematic review and meta-analysis - Li, Xiaoyi; Wang, Yang; Wu, Liu; Zhao, Xinyu; Zhu, Tianmin (Frontiers in Oncology, 2023)
Introduction Tumor-related depression is a series of symptoms or states triggered by a tumor as the basic disease. It does not belong to psychiatric depression but dramatically affects individuals’ quality of life. Acupuncture is extensively used to treat tumor-related depression, but the effect of body acupuncture on tumor-related depression is still unsubstantiated. This work, therefore, set out to assess the effect of acupuncture on tumor-related depression. Methods Eight databases were searched from inception to October 2022 for randomized controlled trials (RCTs). Two researchers separately implemented the database search, study selection, data extraction, and quality assessment. All analyses were performed by using Review Manager 5.3. Results A total of 10 studies, including 725 participants, were included. A majority of studies recruited patients diagnosed with various tumor types and statuses. Meta-analysis revealed that acupuncture had a beneficial effect compared with usual care on the Hamilton depression scale (HAMD) (mean difference (MD) = −2.23, 95% CI [−4.43, −0.03], p = 0.05), self-rating depression scale (SDS) (MD= −6.22, 95% CI [−10.67, −1.78], p = 0.006), effective rate (RR = 1.23, 95% CI [1.06, 1.43], p = 0.006), and quality-of-life questionnaire (QLQ-C30) (MD = 6.08, 95% CI [3.72, 8.43], p<0.0001). In the dimension of the HAMD (MD = −4.41, 95% CI [−6.77, −2.05], p = 0.0002) and SDS (MD = −9.19, 95% CI [−13.14, −5.24], p <0.00001), subgroup analysis also highlighted that acupuncture combined with usual care had an advantage over usual care. However, there was no superiority in acupuncture itself compared to usual care on the HAMD (MD = −1.25, 95% CI [−4.34, −1.84], p = 0.43) and SDS (MD = −3.08, 95% CI [−11.14, 4.98], p = 0.45). Acupuncture also reduced the incidence of adverse effects (RR=0.43, 95% CI [0.23, 0.80], p = 0.008). Conclusion Acupuncture is a safe and effective complementary therapy for tumor-related depression. This technique can provide clinical references for the medical field. Systematic review registration https://www.crd.york.ac.uk/PROSPERO, identifier CRD42022372513.